The Influence Of Value Clarification Technique Learning Models Online Based On Afective Learning Outcomes In Historical Learning - Restu Yanuar Ula; Sarkadi Sarkadi; Aip Badrujaman (Universitas Sebelas Maret, 2020)
The improvement of the quality of education is based on the establishment of the quality of learning and the development of technology. The quality of learning is determined by the competence of teachers in managing the classroom. Online learning with various features and applications can be a great alternative for teachers and students to keep interacting without having to come face to face during covid-19. The online-based VCT learning model can provide critical-creative power, fostering positive attitudes, interests, and grades to students in history learning. Therefore, the purpose of this study is to determine the influence of the online-based Value Clarification Technique learning model on the affective learning outcomes of history students. The research method uses quantitative methods with quasi-experimental designs. The population in this study is all grade XI students of Sma Negeri 9 Bogor City. While the sampling technique is purposive sampling which is divided into two classes into experiment groups (XI IPA 3) and control group (XI IPA 1). The data collection method is a multiple-choice test method. The results of this study show that online-based VCT learning models influence students' affective learning outcomes in historical learning.